Calculați :
a)
![6 \sqrt{3} + 3 \times ( \sqrt{3 } -3 \sqrt{3} ) - 8 \sqrt{3 } = 6 \sqrt{3} + 3 \times ( \sqrt{3 } -3 \sqrt{3} ) - 8 \sqrt{3 } =](https://tex.z-dn.net/?f=6+%5Csqrt%7B3%7D++%2B+3+%5Ctimes+%28+%5Csqrt%7B3+%7D++-3+%5Csqrt%7B3%7D+%29+-+8+%5Csqrt%7B3+%7D++%3D+)
Răspunsuri la întrebare
Răspuns de
1
6 rad3 + 3x(rad3 - 3 rad3) - 8 rad3 =
= 6 rad3 + 3x(-2 rad3) - 8 rad3 =
= 6 rad3 -6 rad3 - 8 rad3 =
= -8 rad3
= 6 rad3 + 3x(-2 rad3) - 8 rad3 =
= 6 rad3 -6 rad3 - 8 rad3 =
= -8 rad3
Răspuns de
1
=6√3+3√3-9√3-8√3=-8√3.Bafta!
Alte întrebări interesante
Limba română,
8 ani în urmă
Ed. muzicală,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă